Microbiome Changes in Healthy Volunteers Treated with GSK1322322, a Novel Antibiotic Targeting Bacterial Peptide Deformylase - Arat, Seda (Antimicrob Agents Chemother, 2015)
GSK1322322 is a novel antibacterial agent under development, and it has known antibacterial activities against multidrug-resistant respiratory and skin pathogens through its inhibition of the bacterial peptide deformylase. Here, we used next-generation sequencing (NGS) of the bacterial 16S rRNA genes from stool samples collected from 61 healthy volunteers at the predosing and end-of-study time points to determine the effects of GSK1322322 on the gastrointestinal (GI) microbiota in a phase I, randomized, double-blind, and placebo-controlled study. GSK1322322 was administered either intravenously (i.v.) only or in an oral-i.v. combination in single- and repeat-dose-escalation infusions. Analysis of the 16S rRNA sequence data found no significant changes in the relative abundances of GI operational taxonomic units (OTUs) between the prestudy and end-of-study samples for either the placebo- or i.v.-only-treated subjects. However, oral-i.v. treatment resulted in significant decreases in some bacterial taxa, the Firmicutes and Bacteroidales, and increases in others, the Betaproteobacteria, Gammaproteobacteria, and Bifidobacteriaceae. Microbiome diversity plots clearly differentiated the end-of-study oral-i.v.-dosed samples from all others collected. The changes in genome function as inferred from species composition suggest an increase in bacterial transporter and xenobiotic metabolism pathways in these samples. A phylogenetic analysis of the peptide deformylase protein sequences collected from the published genomes of clinical isolates previously tested for GSK1322322 in vitro susceptibility and GI bacterial reference genomes suggests that antibiotic target homology is one of several factors that influences the response of GI microbiota to this antibiotic. Our study shows that dosing regimen and target class are important factors when considering the impact of antibiotic usage on GI microbiota. (This clinical trial was registered at the GlaxoSmithKline Clinical Study Register under study identifier PDF 113376.)